Prenatal exposure to multiple metallic and metalloid trace elements and the risk of bacterial sepsis in extremely low gestational age newborns: A prospective cohort study - Bulka, Catherine M.; Eaves, Lauren A.; Gardner, Amaree J.; Parsons, Patrick J.; Galusha, Aubrey L.; Roell, Kyle R.; Smeester, Lisa; O'Shea, T. Michael; Fry, Rebecca C. (Frontiers in Epidemiology, 2022)
Background: Prenatal exposures to metallic and metalloid trace elements have been linked to altered immune function in animal studies, but few epidemiologic studies have investigated immunological effects in humans. We evaluated the risk of bacterial sepsis (an extreme immune response to bacterial infection) in relation to prenatal metal/metalloid exposures, individually and jointly, within a US-based cohort of infants born extremely preterm. Methods: We analyzed data from 269 participants in the US-based ELGAN cohort, which enrolled infants delivered at <28 weeks’ gestation (2002-2004). Concentrations of 8 trace elements – including 4 non-essential and 4 essential – were measured using inductively coupled plasma tandem mass spectrometry in umbilical cord tissue, reflecting in utero fetal exposures. The infants were followed from birth to postnatal day 28 with bacterial blood culture results reported weekly to detect sepsis. Discrete-time hazard and quantile g-computation models were fit to estimate associations for individual trace elements and their mixtures with sepsis incidence. Results: Approximately 30% of the extremely preterm infants developed sepsis during the follow-up period (median follow-up: 2 weeks). After adjustment for potential confounders, only cadmium was individually associated with sepsis risk. Comparing the highest to lowest quartiles, the hazard ratio (HR) for cadmium was 1.88 (95% CI: 0.90-3.93) and there was evidence of a linear dose-response (ptrend=0.04). The HRs for a quartile increase in concentrations of all 8 elements, all 4 non-essential elements, and all 4 essential elements were 0.92 (95% CI: 0.68-1.25), 1.19 (95% CI: 0.92-1.55), and 0.77 (95% CI: 0.57-1.06). Cadmium had the greatest positive contribution whereas arsenic, copper, and selenium had the greatest negative contributions to the mixture associations. Conclusions: Although greater prenatal exposure to cadmium appeared to increase the risk of bacterial sepsis in extremely preterm infants, this risk was counteracted by a combination of arsenic, copper, and selenium. Future studies are needed to confirm these findings and to evaluate the potential for nutritional interventions to prevent sepsis in high-risk infants.